CONTRIBUCION AL ESTUDIO DE LOS SPHECIDAE (HYMENOPTERA) EN LA I REGION DE TARAPACA, CHILE - Porter, Charles C. (Acta Entomológica Chilena, 2022)
A key to the more common predalory wasps of the Family Sphecidae (Hymenoptera) and a list of the species in the Collection of the Institute of Agronomía, Universidad de Tarapacá, 1 Región Arica, Chile, is offered in this paper as a preliminary contribution to the knowledge of these wasps from the Chilean Desert.